Uma análise empírico-exploratória acerca do impacto do teletrabalho na carreira do teletrabalhador - Spritzer, Tiago Almeida (2007)
This dissertation aims at understanding the impacts of telework in the teleworker's career by means of an empiric-exploratory analysis. To this end, we have analyzed the speech of teleworkers of an American multinational company in order to achieve an interpretation capable of identifying common aspects of said speeches. In this process, we have also dealt with issues such as infrastructure, social isolation, productivity, familiar environment, contact with other co-workers, allocation of private and work hours, and elements which motivated the choosing of work option. These factors were highly important for providing a better understanding of the work environment, and for completely covering the impacts of telework in the teleworker¿s career.